The phenomenon of Partisan Cinema: alternative film production in Kazakhstan (Appendix: A Manifesto). (2nd January 2022) - Abishev, Serik; Lumpov, Evgenii; Smailova, Inna
ABSTRACT: This article explores the phenomenon of Partisan Cinema in Kazakhstan in the 2010s in a historical and social context. It explains the funding situation in Kazakhstani film production in order to contextualise the rise of an independent cinema, and places the emergence of socially engaged cinema in the context of early Kazakh experiences with film in the 1930s and the Kazakh New Wave of the late Soviet era. The key films of the movement are analysed, including Adilkhan Yerzhanov's Constructors and The Owners, as well as Zhosulan Poshanov's Toll Bar . The absurdism in Yerzhanov's The Plague at the Karatas Village is singled out and shown as a typical feature of Partisan cinema as it engages with the impossibility of social change, both thematically and stylistically. The framework for this socially engaged cinema is connected to the social realism of the 1950s and 1960s as manifest in the British group of the Angry Young Men. This connection, as well as the principle of Partisan Cinema, are set out in the group's Manifesto of 2014, appended to this article.